Relationships and significance of lactate minimum, critical velocity, heart rate deflection and 3 000 m track-tests for running - Simoes, H. G.; Denadai, B. S.; Baldissera, V; Campbell, CSG; Hill, D. W. (Edizioni Minerva Medica, 2005)
The running velocities associated to lactate minimum (V-lm), heart rate deflection (V-HRd), critical velocity (CV), 3000 M (V-3000) and 10000 m performance (V-10km) were compared. Additionally the ability of V-lm and VHRd on identifying sustainable velocities was investigated.Methods. Twenty runners (28.5 +/- 5.9 y) performed 1) 3000 m running test for V3000; 2) an all-out 500 in sprint followed by 6x800 m incremental bouts with blood lactate ([lac]) measurements for V-lm; 3) a continuous velocity-incremented test with heart rate measurements at each 200 m for V-HRd; 4) participants attempted to 30 min of endurance test both at V-lm(ETVlm) and V-HRd(ETVHRd). Additionally, the distance-time and velocity-1/time relationships produced CV by 2 (500 m and 3000 m) or 3 predictive trials (500 m, 3000 m and distance reached before exhaustion during ETVHRd), and a 10 km race was recorded for V-10km.Results. The CV identified by different methods did not differ to each other. The results (m(.)min(-1)) revealed that V-.(lm) (281 +/- 14.8)< CV (292.1 +/- 17.5)=V-10km (291.7 +/- 19.3)< V-HRd (300.8 +/- 18.7)=V-3000 (304 +/- 17.5) with high correlation among parameters (P < 0.001). During ETVlm participants completed 30 min of running while on the ETVHRd they lasted only 12.5 +/- 8.2 min with increasing [lac].Conclusion. We evidenced that CV and Vim track-protocols are valid for running evaluation and performance prediction and the parameters studied have different significance. The V-lm reflects the moderate-high intensity domain (below CV), can be sustained without [lac] accumulation and may be used for long-term exercise while the V-HRd overestimates a running intensity that can be sustained for long-time. Additionally, V-3000 and V-HRd reflect the severe intensity domain (above CV).
Keywords: lactic acid, blood; critical velocity; exercise intensity domains; running